(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
This paper examines V.S. Naipaul’s A House for Mr. Biswas as a narrative of personal and societal struggle for independence. The protagonist, Mr. Biswas, embarks on a lifelong quest for self-determination, reflected in his desire for a house of his own. Set against the backdrop of post-colonial Trinidad, this work explores themes of identity, autonomy, and belonging. The paper analyzes how Mr. Biswas’s journey symbolizes the broader Caribbean struggle for freedom from colonial oppression. Through an exploration of his character's internal conflicts, familial relationships, and socio-political environment, the research highlights the intersection of personal and national independence. The study also delves into Naipaul’s critique of cultural and economic structures in shaping individual agency. The concept of "home" becomes a metaphor for freedom, and Mr. Biswas’s persistent pursuit offers insight into the complexities of post-colonial identity formation.